Precursor-receptor interactions in the twin arginine protein transport pathway probed with a new receptor complex preparation - Wojnowska, M; Gault, J; Yong, S; Robinson, C; Berks, B (American Chemical Society, 2018)
The twin arginine translocation (Tat) system moves folded proteins across the cytoplasmic membrane of bacteria and the thylakoid membrane of plant chloroplasts. Signal peptide-bearing substrates of the Tat pathway (precursor proteins) are recognised at the membrane by the TatBC receptor complex. The only established preparation of the TatBC complex uses the detergent digitonin, which is unsuitable for biophysical analysis. Here we show that the detergent glyco-diosgenin (GDN) can be used in place of digitonin to isolate homogenous TatBC complexes that bind precursor proteins with physiological specificity. We use this new preparation to quantitatively characterize TatBC-precursor interactions in a fully defined system. Additionally, we show that the GDN-solubilized TatBC complex co-purifies with substantial quantities of phospholipids.